Servicios de telesalud y satisfacción del paciente en el Hospital Iquitos César Garayar García 2021 - Reátegui Gómez, Róger Wálter (2022)
The general objective of the study was to determine the relationship between the telehealth service and patient satisfaction at Hospital Iquitos César Garayar García, 2021, which is why it has been taken as an applied study, descriptive-correlational level and non-experimental design, for which 152 patients were included as a sample, who were surveyed by means of a questionnaire. Well, the following results were achieved: the telehealth service was classified as regular (28%), since the health establishment seldom maintains an updated database of patients, likewise, the health personnel never receive the clinical history with relevant data (name, telephone, address, etc.), on the other hand, sometimes the staff coordinates and establishes the availability of the doctor on duty to attend the patient, also, a notification is rarely sent an hour before the start of the appointment with the doctor to attend him, as well as, the doctor seldom sent him the authorized prescription by email. On the other hand, patient satisfaction was rated as neutral (28%), due to the fact that sometimes the health personnel treats with kindness, likewise, that the consultation never offered adequate and sufficient care, on the other hand, it states that The health personnel almost never provide efficient and effective care, also, that the health personnel never give them confidence and security, in addition, they never provide a good service compared to other institutions, on the other hand, the health personnel to Sometimes it provides personalized attention and finally, it almost never has trained personnel for adequate care. The research work concluded that the relationship (rho = 0.811; p = 0.000) is significant between the telehealth service and patient satisfaction; Similarly, the dimensions of platform (rho = 0.677), appointment management (rho = 0.598), appointment confirmation (rho = 0.520), appointment notification (rho = 0.641) and telemonitoring (rho = 0.593), present a relationship significant (p = 0.000) and considerable with patient satisfaction.